Structural integrity of hierarchical composites - Marco Paggi (Fracture and Structural Integrity)
Interface mechanical problems are of paramount importance in engineering and materials science.Traditionally, due to the complexity of modelling their mechanical behaviour, interfaces are often treated asdefects and their features are not explored. In this study, a different approach is illustrated, where the interfacesplay an active role in the design of innovative hierarchical composites and are fundamental for their structuralintegrity. Numerical examples regarding cutting tools made of hierarchical cellular polycrystalline materials areproposed, showing that tailoring of interface properties at the different scales is the way to achieve superior